Tricobezoar en edad pediátrica - Carpio Cornejo, Juan (2023)
Bezoars are foreign bodies, conglomerates of hair, plant fibers, medications and other substances in the gastrointestinal tract, usually associated with behavioral disorders; The objective of treatment is its removal, associated with the prevention of recurrence. Clinical cases of two female patients, one 11 and the other 12 years old, are presented, who after different auxiliary examinations and medical evaluation, underwent exploratory laparotomy, preceding trichobezoar extraction.